PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AUDIT DELAY - Ratna Wulaningrum; Lewi Patabang; Obed Hamonangan Simatupang (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
The purpose of this study was to determine the effect of profitability, firm size, and institutional ownership on audit delay. The population in this study are manufacturing companies in the mining sector on the Indonesia Stock Exchange in 2017-2021. The method used in sampling is purposive sampling method. The sample in this study from 2017-2021 amounted to 6 companies. The data analysis technique was carried out by descriptive statistical tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The results of this study identified that profitability, firm size, and institutional ownership have no effect on audit delay. Simultaneously, profitability, firm size and institutional ownership have no effect on audit delay in manufacturing companies in the mining sector in 2017-2021.